Implementasi Metode MinMax untuk Mengendalikan Persediaan Produk pada Perusahaan Pakaian Anakling Product Inventory At Umkm Babyje Probolinggo - Wicaksono, Arief Bagus; Wardhanie, Ayouvi; Sudarmaningtyas, Pantjawati (Jurnal Teknik Informatika dan Sistem Informasi, 2024)
Babyje is a Micro, Small, Medium Enterprises that produces children's clothing with a variety of raw materials. Additionally, in the production process, Babyje has Bill of Material data for each of its products. Therefore, product inventory management and raw material requirement planning are important stages in the production process. However, Babyje experienced product supply problems due to unstable market demand. In July 2022 the Babyje experienced stockouts and overstocks with the same percentage, namely 50%, while in August they tended to experience overstocks with a percentage of 80% and in September tended to experience stockouts with a percentage of 70%. This phenomenon can increase storage costs and hinder buyer demand. This study uses the waterfall method for software development and the min max method for product inventory control. The purpose of this research is to produce a product inventory control application using the min max method. The results of implementing the application with the min max method can remind the business when it is the right time to restock, as well as provide recommendations for the number of orders that must be restocked. Based on the results of black box testing with a total of 120 test cases carried out by 2 user roles, all functionality goes well with a 100% success rate, and for user acceptance testing, all user roles have accepted applications with an acceptance percentage of 100%. The results of this application can calculate the difference between the number of orders that should be the number of orders suggested through the system. From the results of these calculations, there is a relative error in system calculations with a percentage of 14.02%.